The Burden of Sub-Saharan African Own Commitments in the Uruguay Round : Myth or Reality? - Sorsa, Piritta (IMF Working Papers; Working Paper, 1995)
The paper reviews Sub-Saharan Africa's (SSA) (i) own market access commitments in the Uruguay Round, and (ii) the nature of the constraints on SSA policies set by the Uruguay Round. It concludes that SSA failed to use the Uruguay Round to lock domestic reforms to an international anchor. Apart from South Africa, most SSA countries made few substantial liberalization commitments on border protection. The new rules set few immediate constraints on SSA policies as developing countries benefit from long and extendable transition periods. The main impact of the new rules will be increased transparency of policies from increased notification requirements. Further trade liberalization will have to rely on unilateral initiatives. This a Working Paper and the author(s) would welcome any comments on the present text. Citations should refer to a Working Paper of the International Monetary Fund, mentioning the author(s), and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.